G protein-coupled receptors: pivotal hubs in gastric cancer malignancy—from multidimensional crosstalk to precision therapeutics - Rong Qin; Xirui Fan; Yun Huang; Yiyao Duan; Hui Wang (Journal of Translational Medicine)
Abstract G protein-coupled receptors (GPCRs), the most extensive group of membrane receptors in humans, are crucial in controlling various physiological and pathological functions. Their involvement in tumorigenesis has garnered increasing attention in recent years. Gastric cancer (GC), which ranks among the most common cancers globally, is closely associated with dysregulated GPCR expression and aberrant signaling pathways. Accumulating evidence demonstrates that multiple GPCRs contribute to GC progression by modulating critical cellular processes—including proliferation, apoptosis, invasion, and metastasis, while establishing complex interplay networks within the tumor microenvironment (TME). However, a systematic understanding of the precise mechanistic actions of GPCRs in GC pathogenesis, along with their potential as diagnostic biomarkers and therapeutic targets, remains elusive. This review comprehensively delineates the expression profiles of GPCRs in GC, their signaling regulatory mechanisms, and dynamic crosstalk with the TME. We critically evaluate the translational value of GPCRs as diagnostic indicators and therapeutic targets, summarize current GPCR-targeted strategies, and propose future research directions to advance precision diagnosis and therapeutic management of GC.